Research on Coded Caching-Enabled Cooperative Transmission Mechanism in LEO Small Satellite Network - Jian LI; Kaiping XUE; Hancheng LU (天地一体化信息网络)
Along with the rapid development of low earth orbit (LEO) small satellite network, users can access content retrieval service through dense-deployed LEO satellite networks in the future.Due to the long propagation delay of satellite-to-terrestrial link, and also the constraint of limited communication resource and energy resource, it is diffi cult for satellites to provide effi cient content transmission service when facing the pressure of onboard overhead.A coded caching-based cooperative transmission mechanism was proposed in dense-deployed LEO small satellite network to achieve effi cient content distribution.By adopting fi ne-grained coded caching scheme, users could simultaneously receive cached packets from multiple LEO satellites to mitigated the cost of satellite backhaul link and improved the caching effi ciency.The simulation results showed that, after deploying onboard caching, the cost of content transmission could be reduced at least 39%.When coded caching-based transmission scheme was adopted, the cost of content transmission could be further reduced by 9%-42% with the increase of satellites providing cooperative transmission.